2011
DOI: 10.1039/c0jm03467c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and catalytic properties of Pd-decorated carbon nanotubes possessing different linkers

Abstract: To investigate the relationship between the linker length and the catalytic activities of metal-decorated CNTs, three samples were prepared with different linker molecules, viz. NaSH, HSCH 2 CH 2 SH, and C 2 H 2 N 2 S 3 . The structures of the prepared samples were characterized using transmission electron microscopy (TEM), powder X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS). The analysis of the TEM images and XRD patterns showed that the Pd nanoparticles strongly adhered to the outside … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Additionally, it is found that the Pd 3d spectrum in Fig. 2(d) consists of four components, which are metallic Pt (335.8 and 341.1 eV), Pd 2þ (337.1 and 342.5 eV), Pd 4þ (338.6 and 343.9 eV) and Pd satellite peak (342.7 eV) [6,35,36]. Compared with the Pd-CB sample (335.2 eV), the Pd peak position of Pd-gCN-CB-30 (335.8 eV) shifted to higher binding energies, which is related to the enhanced attraction force between Pd atoms and g-C 3 N 4 /carbon black support [37,38].…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, it is found that the Pd 3d spectrum in Fig. 2(d) consists of four components, which are metallic Pt (335.8 and 341.1 eV), Pd 2þ (337.1 and 342.5 eV), Pd 4þ (338.6 and 343.9 eV) and Pd satellite peak (342.7 eV) [6,35,36]. Compared with the Pd-CB sample (335.2 eV), the Pd peak position of Pd-gCN-CB-30 (335.8 eV) shifted to higher binding energies, which is related to the enhanced attraction force between Pd atoms and g-C 3 N 4 /carbon black support [37,38].…”
Section: Resultsmentioning
confidence: 96%
“…Nanotubes endowed with thiols 87 , 88 , and 89 , introduced through the carboxylic groups produced after oxidation of the tubes, were among the first modified‐CNT materials used for stabilizing Pd NPs and tested as phosphine free recyclable heterogeneous catalysts in the Suzuki and Sonogashira reactions (Figure ). Esterification or amidation of carboxylic groups have been exploited in order to covalently anchor proper ligands for Pd(II) Schiff base complexes or Pd NPs to oxidized nanotubes for preparing nanocatalysts 90 – 93 .…”
Section: Carbon Nanotubes‐based Catalystsmentioning
confidence: 99%
“…XRD analysis was performed to characterize changes in the crystalline structure of sulfonated MWCNTs. The characteristic diffraction peaks of MWCNTs at 2θ = 25.46° and 2θ = 43.13° represent the hexagonal graphite structure, as shown in Figure (a,b) and Table . The insertion of monomer during modification might destroy the regular stack in MWCNTs, resulting in the disappearance of diffraction peaks at 2θ = 13.69° and 2θ = 13.96° [Figure (a,b)].…”
Section: Resultsmentioning
confidence: 99%